Wnt/β-Catenin Signaling and Obesity - Chen, Na; Wang, Jiqiu (Frontiers in Physiology, 2018)
Obesity has become epidemic worldwide, which triggers several obesity-associated complications. Obesity is characterized by excess fat storage mainly in the visceral white adipose tissue (vWAT), subcutaneous WAT (sWAT), and other tissues. Myriad studies have demonstrated the crucial role of canonical Wnt/β-catenin cascade in the development of organs and physiological homeostasis, whereas recent studies show that genetic variations/mutations in the Wnt/β-catenin pathway are associated with human metabolic diseases. In this review, we highlight the regulation of updated Wnt/β-catenin signaling in obesity, especially the distinctly depot-specific roles between subcutaneous and visceral adipose tissue under high-fed diet stimulation and WAT browning process.